Late Bands Get the Nod from Pan Prelims Judges - Joseph, Terry (Express)
The considerable strain under which Panorama judges perform during preliminary round of competition leaves Pan Trinbago open to claims that its adjudicators may be less than alert during the performances of bands that play late in the programme.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel bands (Music) -- Competitions -- Judging; Steel band music -- Trinidad and Tobago